Glutathione S-transferases in human liver cancer. Issue 12 (December 1991) - Hayes, P C; May, L; Hayes, J D; Harrison, D J
Abstract : An immunohistochemical study of glutathione S-transferase (GST) expression in hepatocellular carcinoma and cholangiocarcinoma is described. Unlike most animal models of hepatic malignancy pi class GST was not consistently overexpressed in hepatocellular carcinoma. This tumour type either predominantly expressed alpha class GST or failed to express GST. By contrast, cholangiocarcinoma always expressed pi class GST, presumably reflecting the tissue of origin, since in human biliary epithelium pi class GST is the predominant GST. The variable expression of pi class GST which was observed in hepatocellular carcinoma may reflect transformation of hepatocytes damaged by toxins, since this GST can be induced after a chemical insult such as alcohol. As well as indicating the biochemical heterogeneity of hepatocellular carcinoma with respect to GST, this study indicates the need for further study of the nature of inherent drug resistance in these tumour types.